Revision Quadriceps Tendon Repair With Bone-Achilles Allograft Augmentation - Navya Dandu BS; Nicholas A. Trasolini MD; Steven F. DeFroda MD; Tai Holland MD; Adam B. Yanke MD, PhD (Video Journal of Sports Medicine, 2021)
Background: Surgical repair of chronic quadriceps tendon ruptures can be daunting, especially after failure of a prior repair. In this setting, tissue quality is usually poor, necessitating graft augmentation. In this video, we describe our technique for Achilles tendon allograft augmentation for revision quadriceps tendon repair. Indications: Failed quadriceps tendon repair defined as ongoing extensor mechanism deficit including patella baja, functional deficit, or palpable quadriceps defect with confirmed retear on advanced imaging. Technique Description: Patient is placed in the supine position, and a midline incision is extended to the tibial tubercle. Full thickness medial and lateral flaps are raised, nonviable scar tissue is excised, and suprapatellar adhesions are released to ensure full mobilization of the viable remnant quadriceps. A plane is then developed deep to the patellar tendon paratenon from proximal to distal. A reamer is used to prepare a socket just medial to the tibial tubercle. The calcaneal bone block of the Achilles allograft is fashioned to match the recipient site on the tibia with a sagittal saw. The graft is shuttled deep to the paratenon, and the bone plug is fixed to the tibia with an interference screw. Suture from the patellar anchors is then used to place 2 running Krackow stitches spanning the remnant quadriceps tendon proximally. The remnant tissue is subsequently reduced and tied with an anchor pull-through technique. The soft tissue component of the Achilles graft is laid over the repair and oversewn with free nonabsorbable suture. Patient is placed in a brace locked in extension for 6 weeks and allowed to be weight bearing as tolerated. Results: Long-term patient-reported outcomes of Achilles allograft reconstruction for revision extensor mechanism repairs are limited. Two studies of 17 reconstructions each reported this to be a reliable and durable option at a mean follow-up of 65 and 52 months, respectively. Discussion/Conclusion: Revision surgery for extensor mechanism deficits can be a challenging procedure. Our preference is to perform augmentation with Achilles allograft with bone plug fixation on the tibial side. This allows for augmentation of the entire extensor mechanism, as well as bone-to-bone healing on the tibial side.